Evaluation of Albumin/Fibrinogen and C-Reactive Protein/Albumin Ratios as Potential Biomarkers of Systemic Lupus Erythematosus - Chanamé Arriola, Luis Alberto (2024)
Introduction: C-reactive protein/albumin (CAR) and albumin/fibrinogen (AFR) ratios are novel biomarkers of inflammation that indicate activity status, severity, and response to treatment in systemic lupus erythematosus (SLE); however, the potential value of these ratios in differentiating SLE patients from healthy individuals has not been evaluated. Objective: To evaluate the value of CAR and AFR as potential biomarkers for differentiation of SLE. Material and methods: Analytical case-control study, performed in a SLE group (n=71) and a control group (n=50). Clinical, inflammatory and cardiometabolic parameters with possible diagnostic value (CAR and AFR) were quantified. The diagnostic threshold was estimated by receiver operating characteristic (ROC) curve, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for each ratio and 95% confidence intervals. Results: The diagnostic thresholds for AFR and CAR were 13.6 and 0.016, respectively. Sensitivity was 53.53% for AFR and 100% for CAR. The specificity was 98% for AFR and 100% for CAR. The ROC curve showed that CAR had a higher area under the curve (AUC) (AUC=1) compared to AFR (AUC=0.76) statistically significant (p<0.001), according to the AUC values, AFR was considered a favorable biomarker and CAR was considered an excellent biomarker to differentiate SLE. Conclusions: CAR is a biomarker with great potential, low cost and easy to measure, which could improve the sensitivity and specificity to diagnose SLE.